Phytogenic Turmeric–Ginger Blend Enhances Nutrient Digestibility and Enzyme Activity in Broiler Chickens - Dyanovita Al Kurnia; Ririn Novita; Fitri Dian Perwitasari (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2026)
This study examined the effects of turmeric–ginger flour supplementation on the digestive enzyme activity of broiler chickens as a natural substitute for synthetic feed additives. The research was motivated by two major challenges in poultry production: the high cost of feed, which contributes to about 60–70% of total expenses, and the growing concern over antibiotic resistance. One hundred one-day-old Lohmann MB Platinum broilers were randomly divided into five groups, each with four replications, receiving 0%, 0.2%, 0.4%, 0.6%, and 0.8% supplementation levels. The birds were raised for 35 days in open cages with free access to feed and water. At the end of the trial, intestinal digesta from the duodenum to the ileum were collected, frozen at −70 °C, and analyzed using spectrophotometric methods to measure amylase, protease, and lipase activities with substrates including 4-nitrophenyl-α-D-glucopyranoside, azocasein, and Tris buffer systems. Results showed a significant dose-dependent increase (P < 0.01) in enzyme activity. The 0.8% treatment yielded the highest values: 105.90 ± 1.05 U/g for amylase, 421.42 ± 6.96 U/g for protease, and 260.70 ± 5.71 U/g for lipase, indicating enhanced digestive performance and nutrient utilization in broilers.